2017
DOI: 10.1093/femsle/fnx048
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal transfer of the blaNDM-1 gene to Pseudomonas aeruginosa and Acinetobacter baumannii in biofilms

Abstract: Horizontal gene transfer has contributed to the global spread of the blaNDM-1 gene. Multiple studies have demonstrated plasmid transfer of blaNDM-1 between Gram-negative bacteria, primarily Enterobacteriaceae species, but conjugational transfer of natural blaNDM-1 plasmids from Enterobacteriaceae into Pseudomonas aeruginosa and Acinetobacter baumannii has not previously been shown. As P. aeruginosa and A. baumannii are both typically strong biofilm formers, transfer of natural blaNDM-1 plasmids could potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…The ability of a dual-species biofilm to spread bla NDM-1 between both clinical and environmental settings was reported. 173 The study confirmed that Enterobacte- riaceae strains could transfer bla NDM-1 readily to strong biofilm-producing P. aeruginosa and A. baumannii in the environment. 173 …”
Section: Beta-lactamasesmentioning
confidence: 52%
“…The ability of a dual-species biofilm to spread bla NDM-1 between both clinical and environmental settings was reported. 173 The study confirmed that Enterobacte- riaceae strains could transfer bla NDM-1 readily to strong biofilm-producing P. aeruginosa and A. baumannii in the environment. 173 …”
Section: Beta-lactamasesmentioning
confidence: 52%
“…The efficacy of combination or alternation therapy is therefore critically dependent upon whether resistance primarily emerges via mutation or the horizontal acquisition of MGEs from exogenous sources (Hughes and Andersson, ). Hence, for some critically resistant pathogens, such as Escherichia coli , Klebsiella pneumoniae , Acinetobacter baumannii and Pseudomonas aeruginosa where the spread of resistance is primarily driven by the transfer of MGEs (McGann et al ., ; Tanner et al ., ), the simultaneous or cyclic use of different antibiotics is unlikely to be an efficient strategy.…”
Section: Discussionmentioning
confidence: 99%
“…There have been multiple reports of HGT of antibiotic resistance genes between species within polymicrobial biofilms. One study found that a plasmid harboring a carbapenemase resistance gene (bla NDM-1 ) can be transferred from E. coli to either P. aeruginosa or Acinetobacter baumannii via conjugation within dual-species biofilms (119), which was not observed between these organisms in planktonic settings (120). These results highlight the enhanced propensity of genetic exchange within biofilms.…”
Section: Interspecies Genetic Exchange Confers Antimicrobial Resistancementioning
confidence: 99%